2016
DOI: 10.26694/reufpi.v5i1.4719
|View full text |Cite
|
Sign up to set email alerts
|

The systemic lúpus erythematosus and women's selfimage carrier / O lúpus eritematoso sistêmico e a autoimagem da mulher portadora / El lupus eritematoso sistémico y el portadora autoimagen de las mujeres

Abstract: Objetivo: identificar as alterações corporais percebidas pelas pacientes lúpicas; analisar a percepção que as pacientes têm de si mesmas diante dessas alterações e elencar as mudanças que essas alterações trouxeram para o seu cotidiano. Metodologia: estudo descritivo-exploratório e abordagem qualitativa, desenvolvido em um Hospital público, em Teresina - Piauí, com 10 pacientes, diagnosticadas com Lúpus Eritematoso Sistêmico, por meio de um roteiro de entrevista semiestruturada, entre 29 de junho e 04 de julho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Some participants in this study reported that alopecia is one of the most impacting skin manifestations because, according to them, its presence causes shame, sadness, isolation and prejudice. Similar results are highlighted in studies carried out in different parts of the world on the experience of living with SLE [9][10][11]20,22 . Impaired physical appearance, body shape, hair and skin, among others, often afflict female vanity, in addition to being a reason for discrimination and deprivation of leisure activities to avoid social exposure, which results in a great impact on the women's quality of life 11,18,23 .…”
Section: /14supporting
confidence: 85%
See 4 more Smart Citations
“…Some participants in this study reported that alopecia is one of the most impacting skin manifestations because, according to them, its presence causes shame, sadness, isolation and prejudice. Similar results are highlighted in studies carried out in different parts of the world on the experience of living with SLE [9][10][11]20,22 . Impaired physical appearance, body shape, hair and skin, among others, often afflict female vanity, in addition to being a reason for discrimination and deprivation of leisure activities to avoid social exposure, which results in a great impact on the women's quality of life 11,18,23 .…”
Section: /14supporting
confidence: 85%
“…Another manifestation arising from illness due to SLE and that negatively interferes in the daily life of sick people is the change in self-image, resulting from skin manifestations, such as skin blemishes, transient and permanent eruptions and alopecia. The literature shows that the negative impact of these manifestations is significantly greater on women, interfering with self-esteem and personal value [9][10][11]20 . However, sometimes, the individuals with SLE feel that these manifestations are not sufficiently valued by the health professionals, as they are related to physical appearance, according to a study carried out on the East coast of the USA 21 .…”
Section: /14mentioning
confidence: 99%
See 3 more Smart Citations